Ap dollio chagi kick's variability by continuous relative phase in elite taekwondo male - Barnamehei, H.; Kharazi, M. (ISBS Proceedings Archive (Michigan), 2017)
This study aimed to investigate the kicking limb coordinative patterns adopted by Taekwondo practitioners (Taekwondoka) during a roundhouse kick (Ap Dollio Chagi). Six Taekwondoka performed five repetitions of both kicks while kicking limb kinematics was recorded using a motion analysis system. Lower-limb coordination was quantified for hip and knee flexion-extension from toe-off to kick completion, using the Continuous relative phase (CRP). For all trials, across all participants, CRP curve peaks and maximum and minimum were determined. The CRP analysis highlighted, during the central portion of both kicks, a delayed flexion of the hip on the knee. Our findings suggested that there were a slight discrepancy in the pattern and variability of inter-joint coordination presented by CRP. This difference may be caused by the velocity (temporal evolution) and the normalization procedure involved in calculating CRP.